PENGARUH KONSEP DIRI AKADEMIS TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI - Rehanja, Maman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe influence of self-concept of academic to student result of class XI IPS in SMA Negeri 1 Sungai Raya Kepulauan, with problem formulation is there influence of academic self concept to result of student learning of class XI IPS in SMA Negeri 1 Sungai Raya Kepulauan. The Method used is associative method with ex-postfacto research, the sample taken is the whole of teh population amounted to 67 student. Date were teken with indirect communication technique(quetionnaire), direct communication(interview), and documentary study(ducument). The test requirements used are validity test and rebility test. Data processing techniques using sample linear regression with the help of SPSS program version 16.0. The results showed that there is a significant influence between self-concept academic on student learning outcomes XI IPS in SMA Negeri 1 Sungai Raya Kepulauan. This can be seen from correlation table which shows that value of significance =0,000 meaning <0,05 with this means there is influence between academic self-concept of student learning outcomes. The persentage of influence of self-concept of academic toward learning result is 55,1% which means student’s learning result is determined by student’s own academic self concept, while the rest 44,9% is determinet by outherfctor which not discussed in this research. Keywords : Academic Self Concepts, Learning Outcomes, Economic Subjects